2005
DOI: 10.1111/j.1369-7625.2005.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the decision‐making preferences of people with colorectal cancer

Abstract: Objectives To explore patient views on participation in treatment, physical care and psychological care decisions and factors that facilitate and hinder patients from making decisions.Design Qualitative study using semi-structured interviews with patients.Setting and participants Three NHS Trusts in the north-west of England. Theoretical sampling including 41 patients who had been treated for colorectal cancer.Results For patients, participation in the decision-making process was about being informed and feeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
60
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 15 publications
2
60
0
Order By: Relevance
“…A previous study reported that patients with CRC wanted to be informed and involved in their care, but did not necessarily want to make any decisions. 1 Another small pilot study of patients with CRC found that more than two-thirds of participants preferred a passive decisionmaking role; however, 80% of patients in the study said that they had not been presented with any treatment alternatives. 26 We found similar results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that patients with CRC wanted to be informed and involved in their care, but did not necessarily want to make any decisions. 1 Another small pilot study of patients with CRC found that more than two-thirds of participants preferred a passive decisionmaking role; however, 80% of patients in the study said that they had not been presented with any treatment alternatives. 26 We found similar results.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused almost exclusively on the physician-patient interaction, with little, if any, emphasis on the impact of familial or cultural factors in the SDM process. [1][2][3][4][5][6][7][8][9][10][11][17][18][19][20][21][22][23][24][25][26][27][28] Patients in our cohort valued family as a crucial adjunct to the health care team, recognizing 3 specific roles for family members (collaborators, interpreters and supporters) that enable and influence decisionmaking while reducing the burden on patients and enhancing their overall experience. Consequently, within a model of patient-centred care, the involvement of family in patient decision-making is an important consideration for surgeons and other health care providers involved in their cancer care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A major disadvantage of pre-operative chemotherapy is the potential for considerable delay before surgery for patients whose tumours prove resistant to Selecting patients for neo-adjuvant therapy and communicating evidence based information is clearly complex, particularly for women diagnosed with more aggressive and/or advanced cancers. It can be argued that surgery, cutting out the problem, is readily understood whereas systemic treatment is more complex to understand (Beaver, Jones, Susnerwala, Craven, Tomlinson, Witham et al 2005). It has been shown that breast care nurses (BCN) are an important source of information and support, helping women cope with their disease (Beaver, Tysver-Robinson, Campbell, Twomey, Williamson, Hindley et al 2009;Cruikshank, Kennedy, Lockhart, Dosser, Dallas 2008,).…”
Section: Exploring Patient Experiences Of Neo-adjuvant Chemotherapy Fmentioning
confidence: 99%
“…Previous qualitative research has shown that patientsÕ views about whether or not they were involved in decision making depended on a variety of factors for example, being informed and feeling involved in the consultation process and not necessarily taking on the responsibility of treatment selection. 26,27 The preference to delegate decision-making responsibility to clinicians was marked amongst heart disease and breast cancer patients. Previous research has shown that a significant proportion of patients with serious illnesses prefer to leave treatment decisions to their doctors.…”
Section: Discussionmentioning
confidence: 99%